Mediating effects of student-perceived instructional practices in the digital gaming-reading performance relationship: a multilevel analysis of PISA 2018 - Goktenturk, Talha; Olusan, Ilayda Seyma (FRONTIERS MEDIA SA, 2026)
Introduction Digital gaming is a prevalent activity among youth, yet its impact on academic outcomes, particularly reading achievement, remains unclear. This study explores how digital gaming behaviors influence reading achievement, focusing on the mediating role of student-perceived instructional practices. Specifically, it examines the contributions of teacher feedback, teacher stimulation for reading engagement, and teacher support as distinct forms of instructional practice, with teacher stimulation conceptualized as an autonomy-supportive instructional practice based on self-determination theory.Methods Using data from 606,627 15-year-old students across 79 countries in PISA 2018, a multilevel structural equation model was employed, incorporating student-level (playing digital games) and school-level (teacher feedback, teacher stimulation, and teacher support) variables. Measurement invariance was evaluated across country, world cultural region, and teacher training standards classifications to examine the cross-group comparability of the instructional-practice measures.Results Results indicate that digital gaming is negatively associated with reading achievement. However, teacher stimulation for reading engagement shows a positive mediating effect, suggesting that autonomy-supportive instructional practices may mitigate the negative association between digital gaming and reading performance. In contrast, teacher feedback and teacher support exhibit weak or negative mediation effects, suggesting that more traditional instructional practices may be associated with less favorable indirect pathways in relation to digital gaming and reading achievement.Discussion Overall, the findings demonstrate that instructional practices differ in their motivational significance and highlight the role of autonomy-supportive stimulation in shaping reading outcomes in contexts where digital gaming is a common out-of-school activity.
Keywords: digital gaming; multilevel structural equation modeling; PISA 2018; reading performance; self-determination theory; student-perceived instructional practices; TEACHER FEEDBACK; GAME ADDICTION; VIDEO GAMES; R PACKAGE; MOTIVATION; LITERACY; GAMIFICATION; PERCEPTIONS; ENGAGEMENT; COMPUTER; Psychology